2015
DOI: 10.1080/15222055.2015.1059913
|View full text |Cite
|
Sign up to set email alerts
|

Tolerance and Avoidance Behavior towards Gas Supersaturation in Rock Carp Procypris rabaudi with a History of Previous Exposure

Abstract: Total dissolved gas (TDG) supersaturation on the upper Yangtze River basin is becoming increasingly serious because of the intense construction of high dams, posing a threat to resident fish. The tolerance and behavior characteristics of Rock Carp Procypris rabaudi preexposed to TDG‐supersaturated water were evaluated by placing juveniles (weight 6.4 ± 1.67 g, fork length 7.2 ± 0.7 cm; mean ± SD) in 35‐cm‐deep tanks at 130% supersaturation for 2.33 h as preexposure. Surviving fish were allowed 5 d of recovery … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
28
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1

Relationship

4
2

Authors

Journals

citations
Cited by 30 publications
(33 citation statements)
references
References 19 publications
3
28
0
2
Order By: Relevance
“…Our results showed that most of the Rock Carp and Prenant's Schizothoracin recovered within 2 d in the saturated-equilibrium water, which is consistent with the results of Dawley and Ebel (1975) and Wang et al (2015b). Wang et al (2015b) placed Rock Carp into 35-cm-deep tanks at 130% supersaturation for 2.33 h and then held them in saturated-equilibrium (100% TDG) water for 5 d. Their results indicated that these fish had a poorer tolerance to TDG-supersaturated water than did the control fish, although their horizontal and vertical behaviors were not significantly different. Our experiment showed that the swimming speed of Prenant's Schizothoracin after 2 d of recovery was significantly lower than that of the control fish, whereas that of the Rock Carp under the same treatment reached baseline levels.…”
Section: Swimming Performance Of Fish After Recoverysupporting
confidence: 92%
See 4 more Smart Citations
“…Our results showed that most of the Rock Carp and Prenant's Schizothoracin recovered within 2 d in the saturated-equilibrium water, which is consistent with the results of Dawley and Ebel (1975) and Wang et al (2015b). Wang et al (2015b) placed Rock Carp into 35-cm-deep tanks at 130% supersaturation for 2.33 h and then held them in saturated-equilibrium (100% TDG) water for 5 d. Their results indicated that these fish had a poorer tolerance to TDG-supersaturated water than did the control fish, although their horizontal and vertical behaviors were not significantly different. Our experiment showed that the swimming speed of Prenant's Schizothoracin after 2 d of recovery was significantly lower than that of the control fish, whereas that of the Rock Carp under the same treatment reached baseline levels.…”
Section: Swimming Performance Of Fish After Recoverysupporting
confidence: 92%
“…Gas bubbles were visible on the fins of the two species in this study, and these fish also suffered mortality within 4 h of TDG supersaturation (15.6% for the Rock Carp and 5.0% for the Prenant's Schizothoracin). The results indicated that Prenant's Schizothoracin was more tolerant of TDG-supersaturated water than were Rock Carp during the 4-h exposure treatment, which was consistent with the results of previous studies (Wang et al 2015a(Wang et al , 2015b.…”
Section: Effect Of Tdg Supersaturation On Fishsupporting
confidence: 92%
See 3 more Smart Citations